Endonasal Access to the Upper Cervical Spine: Part 2—Cadaveric Analysis - Singh, Harminder; Lober, Robert M.; Virdi, Gurpal S.; Lopez, Hector; Rosen, Marc; Evans, James (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objectives The study aims to determine factors that augment endonasal exposure of the cervical spine.Setting We used fluoroscopy and endoscopy to study endonasal visualization of the upper cervical spine.Participants Ten cadavers with normal anatomy were studied.Main Outcome Measures Endoscopic visualization was simulated with projected lines from an endoscope to the cervical spine in multiple positions.Results Neck position alone did not affect the extent of endonasal exposure of the upper cervical spine, although there was a trend correlating the extended neck position with more caudal exposure. The greatest impact was with concurrent use of a 30-degree endoscope and neck extension, and more caudal access was achieved by tilting the endoscope against the piriform aperture, using the posterior tip of the hard palate as the fulcrum.Conclusions Concurrent use of a 30-degree endoscope and neck extension increased the degree of exposure down the cervical spine. Maximum endonasal exposure of the upper cervical spine was obtained by maneuvering instruments at the fulcrum of the posterior hard palate and the nares, rather than changing the position of the neck alone. These results complement radiographic morphometric data in Part 1 of this study for preoperative assessment and surgical planning.
Keywords: cervical spine; endoscopic; minimally invasive; morphometric; odontoidectomy; endonasal